Digital Distribution Channel Management in Enhancing Marketing Efficiency of Creative Products - Muhammad Ridwan Basalamah (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The rapid growth of digital technologies has fundamentally reshaped how products are marketed and distributed, especially in the creative industries. Traditional distribution models, which often relied on physical infrastructure and intermediaries, limited market access and incurred high costs. This study explores the role of digital distribution channel management in enhancing the marketing efficiency of creative products. As the digital landscape evolves, businesses in the creative sector face the challenge of adapting their marketing strategies to leverage digital platforms effectively. This qualitative research employs a literature review methodology to analyze various models and strategies of digital distribution channels that have proven successful in promoting creative products. The findings suggest that the integration of digital distribution channels, including social media, e-commerce, and content platforms, significantly improves marketing efficiency by expanding the reach, reducing costs, and increasing consumer engagement. Furthermore, the study highlights the importance of adopting a multichannel approach to connect with diverse consumer segments, thereby maximizing the impact of marketing efforts. The research contributes to understanding the critical role of digital distribution in the modern marketing ecosystem and offers insights into how creative businesses can optimize their marketing strategies to thrive in a competitive digital economy.